The impact of digital presence on the careers of emerging visual artists - Petrides, L.; Vila de Brito, M. (Social Sciences, 2024)
This paper investigates the importance of digital presence for the emerging visual artists’ careers. The study first examines how artists manage their digital presence and subsequently analyzes the impact of this presence on their careers by applying a model that consists of four objectives (branding, engagement, networking, and conversion). A qualitative method was employed, and interviews were conducted with illustrators at an early or emerging career stage. The findings demonstrate that an effective presence on digital platforms requires not only producing and showing artistic work but also managing an artistic brand, engaging with the audience, and making use of networking opportunities. It is also established that artists need to complement their digital presence with interactions in the physical world to increase the chances for advancing their careers. This paper follows the literature that studies the visual artist as brand manager and adds to the body of knowledge on how artists build successful careers.